Write a DE in the form dy/dt=ay+b ;y=2/3 t->0
1) dy/dt=a(y+b/a)
2)dy/(y+b/a)=a dt
I understand why it integrates as but do not understand why the there is a -ln(c) and not +c on both sids.
3)ln(y+b/a)-ln(c)=a*t

See more answers at brainly.com

Can you take a snapshot of the original problem?

minus ln(c) is still subtract a constant
why can't it take this form?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.